1986
DOI: 10.1017/s0021859600066892
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of nitrogen uptake and its remobilization during the growth of sugar beet

Abstract: The uptake and distribution of N were examined in a series of sugar-beet crops grown on different sites (Broom's Barn, Suffolk and Trefloyne, Dyfed) or with 0 (N o ) or 125 kg N/ha (N m ) between 1978 and 1982. Depletion of soil N was followed in some years.Initial rates of N uptake in spring for the N 126 crops at Broom's Barn ranged from 2-3 kg/ha per day in 1980 to 5-8 kg/ha per day in 1981 and 1982 and at Trefloyne from 4-7 kg/ha per day in 1980 to 5-4 kg/ha per day in 1979. The initial phase of N uptake i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 17 publications
3
13
0
Order By: Relevance
“…It is likely also to be a reflection of the rapid depletion of available nutrients in the upper layers of the soil (e.g. Armstrong et al, 1986;Millard and Robinson 1990).…”
Section: Nutrient Inflow Ratesmentioning
confidence: 99%
“…It is likely also to be a reflection of the rapid depletion of available nutrients in the upper layers of the soil (e.g. Armstrong et al, 1986;Millard and Robinson 1990).…”
Section: Nutrient Inflow Ratesmentioning
confidence: 99%
“…Elevated CO 2 often decreases the concentration of nitrogen-containing components in plants, and the response of sugar beet is important. Sugar beet accumulates glycinebetaine, a quaternary ammonium compound with an osmoregulatory role in halophytes, and compounds containing α-amino-N (amino acids predominantly) with a similar role which may also provide a means of buffering demand for and supply of N during growth (Armstrong et al 1986). These compounds interfere with commercial sucrose extraction (Lohaus, Burba & Heldt 1994) and its economics.…”
Section: Introductionmentioning
confidence: 99%
“…This could be expected, as Armstrong et al . () reported that sugar beet plants might need to take up as much as 5 kg N ha −1 day −1 for rapid leaf expansion. Only a small amount (15–25 kg N ha −1 ) remained in all classes with overlapping ± 1 intervals.…”
Section: Resultsmentioning
confidence: 99%